The Influence of Karaoke Singing on Students’ Pronunciation Accuracy in Reading Aloud - Kusmayadi, Yadi (JOINT: Journal of Inspirational English Language Teaching, 2026)
Technological advancement in information and communication allows learners to have more exposure to English. However, learners with a non-English background, such as Indonesians, have distinctive problems in speaking English, one of which is pronunciation. Integrating karaoke singing into English language teaching and learning is believed to influence learners’ language acquisition, especially pronunciation significantly. This study aims to find the influence of karaoke singing on students’ pronunciation accuracy in reading aloud. This study used a quantitative method through one experimental group involving 23 participants with 10 meetings of intervention of karaoke singing, a pre-test, and a post-test. The pretest and post-test were conducted using ELSA Speak application where the participants were required to read aloud 16 sentences. The participants’ scores were analyzed using univariate and bivariate analysis. The later analysis through t-test provides a p-value of 0.0000 which is lower than the alpha value of 0.05, it leads to the conclusion that there is an influence of karaoke singing on students’ pronunciation accuracy in reading aloud. Hence, it is suggested that teachers or lecturers apply karaoke singing intervention during the class activity to enhance students’ pronunciation accuracy.